Semantic and Lexicographic Differences of Meronymy in Being Compared Languages - Uzbek and English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This thesis is devoted to the meronym and its difference between words and the relationship of comparative analysis in two languages - Uzbek and English. In this, it was expressed about the linguistic and non-linguistic appearance of words between the two languages, how to determine their spiritual relations and their main functional aspects from different point of view.